2014
DOI: 10.1080/0305764x.2013.860080
|View full text |Cite
|
Sign up to set email alerts
|

Teacher preparation in Ethiopia: a critical analysis of reforms

Abstract: The purpose of this article is to provide a more comprehensive picture of teacher preparation in Ethiopia on top of a closer scrutiny of current teacher education reforms. In particular, it presents teacher education within the context of policy implementation over the last six decades by highlighting key reforms and how these reforms impacted the education system in general and the teaching profession in particular. In analysing why and how the policy reforms took place, the paper draws on Chin and Benne's st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 24 publications
(57 reference statements)
2
33
0
Order By: Relevance
“…Similarly, most Ethiopian classrooms still are teacher centered, where informative instruction is the norm (Joshi and Verspoor, 2013). In spite of the rapid expansion of education in general, and higher education in particular, the Ethiopian education system has been experiencing complex hurdles with longterm social, economic, and political implications (Tesfaye, 2014). The lack of genuine commitment to address the glaring problems of education quality in general and the quality of teacher education in particular, seem to manifest faster than many observers might have predicted (Tesfaye, 2014).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
See 3 more Smart Citations
“…Similarly, most Ethiopian classrooms still are teacher centered, where informative instruction is the norm (Joshi and Verspoor, 2013). In spite of the rapid expansion of education in general, and higher education in particular, the Ethiopian education system has been experiencing complex hurdles with longterm social, economic, and political implications (Tesfaye, 2014). The lack of genuine commitment to address the glaring problems of education quality in general and the quality of teacher education in particular, seem to manifest faster than many observers might have predicted (Tesfaye, 2014).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Due to this, the current reality of the education system as a whole, particularly teacher education, has become a source of considerable concern among educators, politicians, and the public at large (Tesfaye, 2014). In order to improve the teacher education program, a number of reforms were introduced and one of the reforms was Teacher Education System Overhaul (TESO) (MoE, 2003).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…Even for those who did pass through formal teacher education, research reviews have identified several problems with the quality of education. These include: out-dated curricula, limited practice-based learning opportunities, weaknesses in the knowledge and expertise of teacher educators and poor institutional management (Hunde & Tacconi, 2014;Semela, 2014). This implies that there was a minimal awareness among stakeholders and rudimentary level of application of active learning and continuous assessment.…”
Section: Teacher and Institution-level Responses To Curriculum Reformmentioning
confidence: 99%